Important performance characteristics in elite grass court tennis: implications for practice - Fitzpatrick, A. (Sheffield Hallam University, 2022)
Notational analysis has become a valued discipline and well-established tool in many sports. Historically, however, notational analysis and its potential for enhancing competitive performance have not been optimised in tennis, with a lack of grass court tennis research and associated practical applications particularly apparent. Additionally, tennis coaches have shown resistance towards technological advancements and are often unsure how to exploit the performance data available to them. In this thesis, a new, user-friendly data analysis method (Percentage of matches in which the Winner Outscored the Loser, PWOL) is developed and validated, to encourage tennis coaches to engage with notational analysis. The method is applied to Wimbledon match-play data, to identify the important performance characteristics in men`s and women`s elite grass court tennis. Points won of 0-4 shot rally length (i.e. short points) is revealed as the most important, so this characteristic is explored further, revealing the critical importance of serving and returning strategies. Accordingly, players` tactical serving and returning behaviours are examined using Hawk-Eye ball-tracking data, with results highlighting that players tend to use first serves to put opponents under positional pressure by aiming for lateral areas of the service box, while opting for safer second serve strategies, typically targeting more central areas. Male winning players were also able to use their serves and serve-returns to force opponents out of position more often than losing players, hitting a comparatively higher percentage of serves and serve-returns to lateral areas of the court. Alongside the novel data analysis method, this thesis advances knowledge around the important aspects of grass court tennis match-play and provides insight into how matches are won at Wimbledon. Designed to inform practice, the practical application facilitates coaches aiming to develop evidence-informed practices for players during the grass court season, ensuring their training is representative of match-play. Implications for performance analysts and high-performance centres are also explored, to promote a more interdisciplinary approach to player development.